2011
DOI: 10.1002/jemt.20910
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of Chinese Materia Medica decoction dregs, Part 1: Comparison of morphological and microscopic features of four Chinese Materia Medica before and after decoction

Abstract: Chinese Materia Medica (CMM) decoction dregs are the residues of medicinal materials after decoction. Accurate identification of CMM in decoction dregs will be helpful for exploring the causes of poisoning or other medical incidents arising after the ingestion of CMM decoctions. To determine how decoction affects the characteristics used to authenticate specific CMM, a systematic study was carried out. In this study, two pairs of Materia Medica that are commonly confused-namely, Baizhu (Atractylodis Macrocepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Authentication of highly processed herbal materials is difficult. Examples include comparison of the morphological and microscopic characteristics of easily confused herbs and their dregs after boiling [ 9 , 10 ]. The approaches described could be useful, but the dregs in a decoction are usually discarded before consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Authentication of highly processed herbal materials is difficult. Examples include comparison of the morphological and microscopic characteristics of easily confused herbs and their dregs after boiling [ 9 , 10 ]. The approaches described could be useful, but the dregs in a decoction are usually discarded before consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Macroscopic characters were noted and taken using visual examination and microscope OLYMPUS SZX12 (Wong et al, 2011(Wong et al, , 2012. Microscopic studies were done by freehand cutting thin section of rhizome with platinum coated razor blade.…”
Section: Methodsmentioning
confidence: 99%
“…That is to say that the identification of decoction dregs of Daqingye and Banlangen has not been reported up to now. Our own studies have found that the normal microscopy reveals little differences between crude drugs and decoction dregs (Wong et al, 2011(Wong et al, , 2012; however, fluorescent microscopy is a different story. In this study, a systematic microscopy investigation on three plant species being sold as Daqingye and Banlangen, namely I. indigotica, B. cusia, and C. cyrtophyllum, including crude drugs and decoction dregs, was carried out by combining normal light microscopy with fluorescence microscopy, which with the purpose of providing scientific data for the identification of crude drugs and decoction dregs, and then ensuring the safe and effective application of Daqingye and Banlangen.…”
Section: Introductionmentioning
confidence: 93%
“…That is to say that the identification of decoction dregs of Daqingye and Banlangen has not been reported up to now. Our own studies have found that the normal microscopy reveals little differences between crude drugs and decoction dregs (Wong et al, ); however, fluorescent microscopy is a different story. In this study, a systematic microscopy investigation on three plant species being sold as Daqingye and Banlangen, namely I .…”
Section: Introductionmentioning
confidence: 98%